Peningkatan Kualitas Hidup Masyarakat Kampung dengan Pemanfaatan Internet Sebagai Sarana Pembelajaran dan Promosi Wisata di Kampung Maribu, Distrik Sentani Barat, Kabupaten Jayapura - Abd. R. Dayat; Liza Angriani; Nelly A. Fonataba (LPPM Uncen, 2025)
Kampung Maribu has several natural tourism potentials that unfortunately have not developed well due to several factors. One of the natural beauties of Kampung Maribu that is still unknown to many people is Gunung Iroy, also known as Gunung Kabut, which is one of the most beautiful tourist destinations in Kampung Maribu. In addition to its tourism potential, Kampung Maribu is the center of the largest sago forest in Jayapura Regency and is located at the end of the West Sentani District. The charm of Papua orchids holds a special place for orchid enthusiasts. The exotic shapes and types of orchids, along with their limited distribution, make Papua orchids highly sought after by orchid collectors. The condition of the partner in terms of regional potential and the community that has been described is that there are many potentials that can be developed, but due to the limited human resources available for promotion, it has not been optimally developed. Therefore, the improvement of the quality of life for the village community through the use of the internet as a means of learning and promoting tourism in Kampung Maribu, Sentani Barat District, Jayapura Regency, needs to be carried out. The results obtained after the installation of free internet access for Kampung Maribu are as follows: the level of understanding among the people of Kampung Maribu has increased, as shown in the questionnaire results indicating an average understanding increase of 68.56%. This is because the community has become more active in accessing information for learning through YouTube portals and Blogs/Forums, the increasing number of local tourists from around Jayapura City and Jayapura Regency visiting potential tourist sites in Kampung Maribu, the growth of local MSMEs that have started actively marketing their products through social media, and the active use of the village hall in activities because it has become a center for free internet services for the community.